EFFICACY OF HYDROALCOHOLIC EXTRACT OF ACORUS CALAMUS LINN. IN THE MANAGEMENT OF HYPOTHYROIDISM IN ALBINO WISTAR RATS – A REVIEW - MEHDI, HIDAYATH KHAN; BEGUM, ZAKERA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
The objectives of this study were to evaluate the efficacy of hydroalcoholic extract of Acorus calamus Linn (HAEAC), in drug-induced hypothyroidism in albino Wistar rats, to prove the scientific integrity, credibility, and reliability of the concepts of the Unani system of medicine in the present era, to manage the disease with safe, low-cost, effective, and easily available drugs in the Unani system of medicine, and to compare the test drug with the standard control drug in the management of hypothyroidism. Thirty female albino Wistar rats were used in the study. The rats were divided into six groups and three animals were in each group. G1 – Control group, G2 – Negative group, G3 – Standard group, G4 – Low test dose, G5 – Medium test dose group, and G6 – High test dose group. Except control group, all the rats were given propylthiouracil (PTU)-10 mg/kg/day, oral route for 30 days to induce hypothyroidism. The HAEAC used for the study. Toxicity study was done according to Organization for Economic Co-operation and Development 423 guidelines for the pilot study. Moreover, then the dose of the test drug was fixed as low dose (200 mg/kg/bw), medium dose (400 mg/kg/bw), and high dose (600 mg/kg/bw).The effect of test drug Waj (HAEAC) in PTU-induced hypothyroidism, in high test dose (600 mg/kg/bw) results, shows the Mean±Standard deviation of T3 is 91.667±2.517 (p<0.001), T4 is 4.700±0.200 (p<0.01), and TSH is 26.033±7.061 (p<0.01).